Implementation Plan in Response to the Board-Endorsed Recommendations from the IEO Evaluation Report on IMF Advice on Unconventional Monetary Policies. (Policy Papers; Policy Paper, 2020)
This Management Implementation Plan was prepared before COVID-19 became a global pandemic and resulted in unprecedented strains in global trade, commodity and financial markets. The actions in the plan and their timeline, therefore, do not reflect the implications of these developments and related policy priorities. This MIP includes a package of self-reinforcing actions that aim to: -- Strengthen in-house expertise on monetary policy -- Deepen the work on UMP and related policies -- Further strengthen financial spillover analysis -- Explore ways to enhance the Fund's traction.